Photocurrent generation in single electron tunneling transistors - Tageman, Ola (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1999)
A single-electron tunneling transistor (SET) with a non-equilibrium mode population in one of the leads is analyzed theoretically. We model transport through a dot coupled to a channel, both formed by gates from the two-dimensional electron gas of a GaAs/AlGaAs heterostructure. The non-equilibrium mode population, which is induced by coherent THz-pumping in the channel, produces empty states below the Fermi level for electrons to tunnel into. A photocurrent arises, which is periodically saw-tooth peaked with respect to the voltage on a central gate. For intense THz-fields the peaks display plateaus that reflect the energy dependence of the mode population. We also predict a high-gain Vin/Vout transfer-characteristic, similar to that of a current biased SET.